Key Challenges for Indigenous Peoples of Canada in terms of Oral Health Provision and Utilization: A Scoping Review - Ahmed Hussain (International Journal of Dentistry)
Background. The oral health of Indigenous peoples in Canada is lacking compared with their non-Indigenous counterparts. This scoping assessment aimed to investigate the obstacles of providing and using oral healthcare among Indigenous peoples in Canada. Methods. The scoping review took place between December 15, 2021 and January 10, 2022. Five key databases were examined: PubMed, Scopus, ISI Web of Science, Embase, and PROQUEST. The data were analyzed using NVIVO software to facilitate understanding of the major themes, subthemes, and codes provided. Results. Seven major themes and eighteen subthemes were identified as impacting the oral health provision and utilization of Indigenous peoples in Canada. The major themes are individual characteristics, affordability, availability, accessibility, accommodation, acceptability, and public or government policy. Thus, to improve the oral health of the Indigenous peoples in Canada, an integrated approach is required to address these obstacles. Conclusions. To address the oral health disparities among Indigenous peoples in Canada, policymakers should adopt an integrated approach.